THE EFFORTS TO INCREASE THE INTELLECTUAL ABILITY AND COMMUNICATION IN LEARNING OF MATHEMATICS USING THINKING ALOUD PAIR PROBLEM SOLVING (TAPPS) METHOD OF VII GRADE STUDENTS OF SMP NEGERI 2 BINANGUN CILACAP - Fiska Nur Indah; Uus Kusdinar (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
This research is implementable because of the low intellectual ability and communication of the students in learning mathematics. The objective of this research is to try to increase the intellectual ability and communication of VII grade students in semester II of SMP Negeri 2 Binangun Cilacap in the academic year 2015/2016 using Thinking Aloud Pair Problem Solving (TAPPS) method. This research is a Classroom Action Research which consists of two-cycle, where each cycle consists of two meetings. The subject of this research is the students of VII B in the second semester of SMP Negeri 2 Binangun Cilacap in the academic year 2015/2016 which consists, 32 students, there are 16 male students and 16 female students. The object of this research is the intellectual ability and communication using the Thinking Aloud Pair Problem Solving (TAPPS) learning process. The data accumulation technic used observation, interview, test, triangulation, documentation, and field notes. The data analysis used descriptive qualitative analysis. The result of the research showed that the mathematics learning using Thinking Aloud Pair Problem Solving (TAPPS) method was able to increase the intellectual ability and communication of VII grade students in semester II of SMP Negeri 2 Binangun Cilacap. The result of the observation assessment sheet in cycle I the percentage of intellectual ability belonged to the good category (67,88%) and the percentage of communication ability belonged to the fair category (58,59%). In cycle II, the percentage of the intellectual ability belonged to a very good category (87,97%) and the percentage of the communication ability was belonged good category (75,78%).